UJI EFEK HIPOGLIKEMIK EKSTRAK ETANOL DAUN LIDAH BUAYA (Aloe vera L.) TERHADAP KADAR GLUKOSA DARAH TIKUS PUTIH (Rattus norvegicus) JANTAN GALUR WISTAR YANG DIINDUKSI ALOKSAN - ., Esteria Roslina Hutabarat (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Diabetes mellitus is a group of metabolic diseases characterized byhyperglycemia. Gel from lidah buaya leaves (Aloe vera L.) contain secondarymetabolites compound which reduce blood glucose level. Objective: The aim ofthis study is to investigate the hypoglycemic effect and find effective dose ofethanolic extract from lidah buaya leaves on male wistar rats after alloxaninduction compared with metformin as positive control. Method: The researchwas a randomized pre-test post-test controlled group design experiment. Thirtywistar rats was randomly divided into 5 experimental group, negative control(CMC 0,5%), positive control (metformin), dose I (250 mg/k gBW), dose II (500mg/kgBW, and dose III (1000 mg/kgBW). All groups were induced with alloxan toa glucose level approximately more than 200 mg/dl. Treatments wereadministered for 7 days. The data were analyzed by One-way Anova testcontinued with LSD Post Hoc test. Result: From the phytochemical screeningresult, lidah buaya leaves ethanolic extract contain flavonoid, alkaloid, saponin,glycoside. Statistical analysis showed significant difference between averageglucose level from control group (negative and positive) against dose I group,dose II group and dose III group (p<0,05) at day-8. Significant differencebetween dose I group and dose II group, dose I group and dose III group, dose IIgroup and dose III group, is not found Conclusion: Ethanolic extract from lidahbuaya leaves has hypoglycemic effect better than metformin on white male wistarrats after alloxan induction with effective dose at 250 mg/kgBW.Key Words: Aloe vera L., blood glucose level, ethanolic extrct from lidah buayaleaves, alloxan induction1)Medical School, Faculty of Medicine, Universitas Tanjungpura Pontianak,Kalimantan Barat2)Department of Pharmacology, Medical School, Faculty of Medicine,Universitas Tanjungpura Pontianak, Kalimantan Barat3)Departement of Community Health, Family Health and Public Health,Medical School, Faculty of Medicine, Universitas Tanjungpura Pontianak,Kalimantan Barat